Should Microhematuria Be Incorporated into the 2023 Duke-International Society for Cardiovascular Infectious Diseases Minor Immunological Criteria? - Jean Regina; Louis Stavart; Benoit Guery; Georgios Tzimas; Pierre Monney; Lars Niclauss; Matthias Kirsch; Dela Golshayan; Matthaios Papadimitriou-Olivgeris (Antibiotics)
Background/Objectives: Microhematuria is common in patients with infective endocarditis (IE). The present study aims to assess whether the addition of microhematuria in the 2023 Duke-International Society for Cardiovascular Infectious Diseases (ISCVID) minor immunological criteria could enhance its diagnostic performance. Methods: This retrospective study was conducted at the Lausanne University Hospital, Switzerland (2014–2024). All patients with suspected IE and urinalysis within 24 h from presentation were included. The Endocarditis Team classified episodes as IE or non-IE. Microhematuria was defined as >5 red blood cells per high power field (HPF). Results: Among 801 episodes with suspected IE, 263 (33%) were diagnosed with IE. Microhematuria (>5/HPF) was present in 462 (58%) episodes, with no difference between episodes with and without confirmed IE (61% versus 56%; p = 0.223). Based on the 2023 ISCVID-Duke, minor immunological criteria were present in 42 episodes (5%). By adding microhematuria, 473 (59%) episodes met the minor immunological criteria. Sensitivity of the clinical criteria of the 2023 ISCVID-Duke version without and with hematuria was calculated at 75% (69–80%) and 86% (81–90%), respectively. Specificity was at 52% (48–57%) and 40% (36–45%), respectively. Among episodes with suspected IE, microhematuria was associated with female sex, enterococcal bacteremia, sepsis or septic shock, acute kidney injury, non-cerebral embolic events, and bone and joint infection. Conclusions: Microhematuria was frequent among patients with suspected IE, but it was not associated with the diagnosis of IE. The addition of microhematuria in the 2023 ISCVID-Duke minor immunological criteria did not enhance the overall performance of the criteria.